Serological and Molecular Testing in Viral Hepatitis: An Update - Shiobhan R Weston; Paul Martin (Canadian Journal of Gastroenterology)
The routine serological diagnoses of the three major forms of viral hepatitis - A, B and C - as well as delta hepatitis, are important in the evaluation of acute and chronic viral hepatitis. Increasingly, molecular virology is also being used to evaluate patients with chronic hepatitis C, with genotype and viral load testing to plan therapy.